Assessment of Assertiveness and Self Esteem among Nursing Students in Selected Nursing Colleges: A Systematic Review - Shilpa1 , Shalini2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Assertive behaviour promotes a feeling of personal power and self-confidence. These twocomponents are commonly lacking in individual/students. Becoming more assertive empowers individualsby empowering self-esteem, without diminishing the esteem of others. Purpose: To systematically reviewthe articles to assess assertiveness among nursing students in selected Nursing colleges. Method: The searchof significant articles including assertiveness and its correlates among nursing students was carried out inPubMed/Medline, Google Scholar and other databases. It includes both Qualitative and Quantitative studieswere evaluated according to predefined quality criteria. Medline and PubMed were searched to identifypeer-reviewed English-language studies published between 1985 and March 2018 reporting Assertivenessamong nursing students. Total 250 studies were selected for review, out of which only 30 Studies were foundappropriate to be included in the study. Results: Analysis was done 90 papers were retrieved by the search.Among them, 30 were evaluated to be of higher quality. These Studies included sample of nursing studentsand excluded Non Nursing Students. Conclusion: Based on the review it was concluded that the level ofassertiveness among nursing students studying in advanced Semesters was increased slightly as compared tothose displayed by first-semester. It was also concluded that concluded that there was significant correlationfound between the assertiveness and academic achievement and with self- esteem.